Health facility factors influencing the waiting time among pregnant mothers attending antenatal clinic at Kira Health Centre IV, Wakiso District. A cross-sectional study. - Shifa Mugide; Patrick Ssendugga; Grace Denise Akwang; Suzan Oyesigye; Jacob Usuo Kibuuka (SJ Gynecology and Obstetrics Africa, 2026)
Background: This study aimed to assess health facility factors influencing waiting time among pregnant mothers attending antenatal clinic at Kira Health Centre IV, Wakiso District. Methodology: A descriptive cross-sectional study using quantitative data collection methods was conducted among pregnant mothers attending antenatal care at Kira Health Centre IV. 80 respondents were selected using simple random sampling, and data were collected using interviewer-administered structured questionnaires. Data were coded, entered and analysed in Microsoft Excel. Results were presented using frequencies, percentages, tables, graphs and charts. Results: 34(42.5%) of the respondents were aged 18 – 25 years, while 4(5%) were aged above 45 years. The majority of the respondents, 51(63.7%), had attained secondary education; 7(8.8%) had never gone to school, 59(73.8%), were married, while 2(2.5%), were divorced. 42(52.5%), were unemployed; 3(3.8%), belonged to public employment. 36(45%), were Catholics; 2(2.5%), were Seventh-day Adventists. 40(50%) respondents spent 1–2 hours at the registration desk while obtaining their antenatal cards, whereas only 7(8.8%) spent less than 30 minutes. 44(55%) reported that health workers never communicated about the flow of services. 58(72.5%) reported that signposts or arrows were present in some departments, while 9(11.2%) reported that none were present. 48(60%) perceived the speed of health workers as slow, and 68 (85%) reported that the antenatal clinic was understaffed. Conclusion: Delays at registration, inadequate communication about service flow, limited directional signage, slow movement of health workers, and understaffing were the major health-facility factors associated with prolonged waiting times. Recommendation: More health workers should be recruited, directional signs should be installed in all departments, and health workers should improve communication about service flow and timely delivery of antenatal services.